(untitled) (Research, Society and Development, 2020)
Currently, the success of rehabilitation with implants has aroused in patients the interest and hope to smile again after having undergone tooth extractions in the past, and for the fact of not adapting to the use of conventional dental prostheses for a long time. The segmental maxillary osteotomy procedure is a viable treatment proposal for patients who present a decrease in the anterior vertical dimension of the maxilla, due to the chronic resorptive process in the region, making implant-supported rehabilitation more satisfactory. In view of the need to correct maxillary discrepancies in a single surgical procedure, some aspects must be taken into account, such as: patient selection, surgical and prosthetic planning and the determination of a more predictable type of treatment, from the patient’s perspective. The objective of this work is to report a clinical case of a patient who underwent segmental osteotomy en bloc of the anterior region of the maxilla, prior to implant-supported rehabilitation. A female patient came to the service complaining of discomfort due to using dental prosthesis for a long time. Upon initial clinical and imaging examination, the need to increase bone height in the anterior region of the maxilla was found. It was proposed for the case to perform a segmental osteotomy of the anterior region of the maxilla to gain bone height in the region that allowed a functional and aesthetic rehabilitation for the patient. With this case, it can be concluded that the block segmental osteotomy procedure of the anterior region of the maxilla for aesthetic correction is effective and requires adequate planning to obtain satisfactory aesthetic results.